The Relationship Between Family Environment in Education and Students' Achievement in Elementary School (A Literature Review) - Suparlan (Formad English Foundation NTB Jakarta, 2025)
This study investigates the influence of the family environment on students' academic performance in elementary schools. The research explores how various components of the family environment, such as parental involvement, socioeconomic status, parent-child communication, and the home learning environment, contribute to academic success. Using a qualitative literature review approach, the study synthesizes existing research and identifies key factors affecting academic outcomes. Findings indicate that parental engagement, effective communication, and a structured home environment positively impact students’ academic achievement. Furthermore, socioeconomic status was found to be a significant factor in determining access to educational resources, with higher SES families providing better support for learning. The study emphasizes the importance of fostering a supportive family environment to optimize academic success and offers actionable insights for educators and parents to enhance students' learning experiences. These findings contribute to educational psychology and suggest further research to explore the mechanisms through which family environments influence academic outcomes.